Quantifying decoration interaction : a study of the decoration on the cult chapel walls of the Old Kingdom tombs at Giza - Roeten, Leo. (Culture and History of the Ancient Near East, 2014)
In The Decoration on the Cult Chapel Walls of the Old Kingdom Tombs at Giza Leo Roeten presents a method that evaluates the degree of interaction between the various decoration themes that are placed on the western wall of the cult chapels at the tombs of Giza. Diagrams resulting from that method show that during the 5th dynasty the focus of the mode of food supply for the ka of the deceased changed from primarily active to primarily magical. On the other walls of the chapel this change not only led to the loss of some secondary cultic functions like the inviting and guiding functions, but also to an increasing focus on scenes from the daily life of the tomb owner.